Morphological and Molecular Identification of Pennate Diatoms Isolated From Urla, Izmir, Coast of the Aegean Sea - Kesici, Kutsal; Tüney, İnci; Güden, Mustafa; Sukatar, Atakan; Zeren, Doğuş; Güden, Mustafa (TUBITAK, 2013)
Diatoms represent an important class of aquatic phototrophs. They are not only one of the major contributors to global carbon fixation, but also play a key role in the biogeochemical cycling of silica. Molecular identification methods based on conserved DNA sequences, such as ITS (Internal Transcribed Spacer) have revolutionized our knowledge and understanding of conventional taxonomy. In this study, we aimed to compare the conventional identification methods with molecular identification methods. To do so, we isolated four diatom samples from Coast of Urla and characterized them using light microscopy (LM) and scanning electron microscopy (SEM) according to morphological features. Then, we amplified ITS regions using conventional polymerase chain reaction (PCR), sequenced the PCR products and analyzed the sequences using bioinformatic tools. Bioinformatic analysis indicated that the isolated species had high sequence similarity to Pseudo-nitzschia sp., Achnanthes sp., Amphora sp. and Cylindrotheca sp. We believe that molecular identification methods enable rapid and more reliable identification of diatom species and are crucial for monitoring harmful algal blooms.

Diatomlar denizsel ortamın oldukça önemli bir fotosentetik organizma grubudur. Küresel karbon fiksasyonunun baskın elemanları olmalarının yanısıra silikanın biyokimyasal döngüsünde de önemli bir rol oynamaktadırlar. Günümüzde sistematik ve evrimsel çalışmalarda ITS (Internal Transcribed Spacer) bölgesine dayalı DNA analizleri standart bir yaklaşım halini almış ve bu alana yeni bir bakış açısı getirmiştir. Bu çalışmada geleneksel tayin yöntemleri ile moleküler tayin yöntemlerininin karşılaştırılması amaçlanmıştır. Bu nedenle Urla kıyılarının farklı bölgelerinden dört diatom türü izole edilmiş, ışık mikroskobu (LM) ve taramalı elektron mikroskobu (SEM) ile morfolojik olarak incelenmiştir. Daha sonra ITS bölgesi PZR (Polimeraz Zincir Reaksiyonu) yöntemi ile çoğaltılmış, elde edilen PZR ürünlerinin dizi analizi yapılarak biyoinformatik yöntemler kullanılarak tür tayini gerçekleştirilmiştir. DNA dizi analizi sonuçlarına göre izole edilen diatomların Pseudo-nitzschia sp., Achnanthes sp., Amphora sp. ve Cylindrotheca sp.. oldukları saptanmıştır. Moleküler yüntemlerle gerçekleştirilen tür tayinlerinin, diyatom türlerinin belirlenmesi ayrıca zararlı ani alg çoğalmalarının izlenmesi açısından da daha hızlı ve güvenilir olduğu kanısındayız.
Urla-izmir (ege Denizi) Kıyılarından İzole Edilen Pennate Diatomların Morfolojik ve Moleküler Tayini
Keywords: Diatom; ITS; LM; Sem; Molecular characterization